2018
DOI: 10.2215/cjn.02450218
|View full text |Cite|
|
Sign up to set email alerts
|

Associations with Wellbeing and Medication Adherence in Young Adults Receiving Kidney Replacement Therapy

Abstract: Background and objectives Young adults receiving kidney replacement therapy (KRT) have impaired quality of life and may exhibit low medication adherence. We tested the hypothesis that wellbeing and medication adherence are associated with psychosocial factors.Design, setting, participants, & measurements We conducted a cross-sectional online survey for young adults on KRT. Additional clinical information was obtained from the UK Renal Registry. We compared outcomes by treatment modality using age-and sex-adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 32 publications
3
40
1
1
Order By: Relevance
“…Consequently, the experiential bene ts of the arts-based intervention more accurately address the core components of Seligman's PERMA model of wellbeing. [50] Patients with kidney disease have lower levels of mental wellbeing compared to the general population [52], and this is associated with higher levels of mental illness. However, mental wellbeing is a topic that is rarely explored in nephrology, in part due to the focus on physical health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the experiential bene ts of the arts-based intervention more accurately address the core components of Seligman's PERMA model of wellbeing. [50] Patients with kidney disease have lower levels of mental wellbeing compared to the general population [52], and this is associated with higher levels of mental illness. However, mental wellbeing is a topic that is rarely explored in nephrology, in part due to the focus on physical health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The survey comprised questions from validated health surveys (described next) with available comparable normative data. Additional scales and tools covering aspects of chronic disease were also included (reported separately 8 ). The study was granted ethics approval by the Health Research Authority National Research Ethics Service Committee South West-Cornwall & Plymouth, reference 15/SW/0101.…”
Section: Methodsmentioning
confidence: 99%
“…29 It has been stated that social support led to a better life, reduced depression, and resulted in more efficient coping with the disease in patients under hemodialysis, while weak social support could increase mortality. 30 Indeed, social support was associated with the hemodialysis patients' QoL, 31 which not only protected them against tensions caused by the illness, but also increased their social-mental coping level. 32 It has also been found that low levels of social support increased mortality and reduced QoL in patients under hemodialysis.…”
Section: Introductionmentioning
confidence: 99%